A Process for Setting, Managing, and Monitoring Environmental Windows for Dredging Projects: Special Report 262 - Transportation Research Board (The National Academies Press, 2002)
TRB Special Report 262: A Process for Setting, Managing, and Monitoring Environmental Windows for Dredging Projects concludes that scientific information about risks to resources and technical options for reducing those risks was not being systematically incorporated into the dredging process. The process itself is complex and time-consuming because of the numerous federal and state agencies and interest groups involved. The committee recommended use of a broad-based decisionmaking process designed to engage stakeholders more effectively and to improve the scientific and technical basis for the decisions made. Environmental windows are periods in which regulators have determined that the adverse impacts associated with dredging of waterways and disposal of the dredged materials can be reduced below critical thresholds, and dredging is therefore permitted. Conversely, seasonal restrictions are applied2014dredging and disposal activities are prohibited 2014when the perceived increase in potential harm to aquatic resources is above critical thresholds. Since passage of the National Environmental Policy Act of 1969, resource agencies have requested environmental restrictions on dredging with increasing frequency. Today, more than 80 percent of federal contract dredging is subject to some type of restriction. At the request of the U.S. Army Corps of Engineers, TRB and the National Academies' Ocean Studies Board convened a committee to address concerns about the decision-making process for setting environmental windows. Windows are intuitively simple means of reducing risk to biological resources from stressors generated during dredging and disposal activities, including entrainment of fish eggs and larvae, resuspension of contaminated sediments, habitat loss, and collisions with marine animals. The use of windows as a management tool, however, can have significant cost implications for both the U.S. Army Corps of Engineers and the local sponsors of dredging projects, delay project deadlines, and increase risk to dredging personnel by shifting projects to periods of potentially inclement weather and sea states.Special Report 262 Summary

Evaluation of Cyclamate for Carcinogenicity (The National Academies Press, 1985)

Standing Operating Procedures for Developing Acute Exposure Guideline Levels for Hazardous Chemicals - National Research Council (The National Academies Press, 2001)
Standing Operating Procedures for Developing Acute Exposure Guideline Levels for Hazardous Chemicals contains a detailed and comprehensive methodology for developing acute exposure guideline levels (AEGLs) for toxic substances from inhalation exposures. The book provides guidance on what documents and databases to use, toxicity endpoints that need to be evaluated, dosimetry corrections from animal to human exposures, selection of appropriate uncertainty factors to address the variability between animals and humans and within the human population, selection of modifying factors to address data deficiencies, time scaling, and quantitative cancer risk assessment. It also contains an example of a summary of a technical support document and an example of AEGL derivation. This book will be useful to persons in the derivation of levels from other exposure routes2014both oral and dermal2014as well as risk assessors in the government, academe, and private industry.

Toxicity Testing: Strategies to Determine Needs and Priorities - National Research Council (The National Academies Press, 1984)
Prepared at the request of the National Toxicology Program, this landmark report reveals that many chemicals used in pesticides, cosmetics, drugs, food, and commerce have not been sufficiently tested to allow a complete determination of their potential hazards. Given the vast number of chemical substances to which humans are exposed, the authors use a model to show how research priorities for toxicity testing can be set.

Possible Long-Term Health Effects of Short-Term Exposure to Chemical Agents: Volume 1 (The National Academies Press, 1982)

The Ozone Depletion Phenomenon (The National Academies Press, 1996)
Like an infection that grows more and more virulent, the continent-size hole in Earth's ozone layer keeps getting bigger and bigger. Each year since the late 1970s, much of the protective layer of stratospheric ozone above Antarctica has disappeared during September, creating what is popularly known as the ozone hole. The Antarctic hole now measures about 9 million square miles, nearly the size of North America. Less dramatic, still significant, depletion of ozone levels has been recorded around the globe. With less ozone in the atmosphere, more ultraviolet radiation strikes Earth, causing more skin cancer, eye damage, and possible harm to crops. What is ozone? How did researchers discover its role in Earth's atmosphere and the devastating consequences of its depletion? The following article, adapted from an account by Dr. F. Sherwood Rowland, a pioneering researcher in the field who shared the 1995 Nobel Prize in Chemistry for his work, attempts to answer these and other questions. In doing so, it dramatically illustrates how science works and, in particular, how basic research2014motivated by a desire to understand nature2014often leads to practical results of immense societal benefit that could not have been anticipated when the research first began.

Animals as Sentinels of Environmental Health Hazards - National Research Council (The National Academies Press, 1991)
Studying animals in the environment may be a realistic and highly beneficial approach to identifying unknown chemical contaminants before they cause human harm. Animals as Sentinels of Environmental Health Hazards presents an overview of animal-monitoring programs, including detailed case studies of how animal health problems2014such as the effects of DDT on wild bird populations2014have led researchers to the sources of human health hazards. The authors examine the components and characteristics required for an effective animal-monitoring program, and they evaluate numerous existing programs, including in situ research, where an animal is placed in a natural setting for monitoring purposes.

Assessment of Exposure-Response Functions for Rocket-Emission Toxicants - National Research Council (The National Academies Press, 1998)
The U.S. Air Force is developing a model to assist commanders in determining when it is safe to launch rocket vehicles. The model estimates the possible number and types of adverse health effects for people who might be exposed to the ground cloud created by rocket exhaust during a normal launch or during an aborted launch that results in a rocket being destroyed near the ground. Assessment of Exposure-Response Functions for Rocket-Emmission Toxicants evaluates the model and the data used for three rocket emission toxicants: hydrogen chloride, nitrogen dioxide, and nitric acid.

Marine Biotechnology in the Twenty-First Century: Problems, Promise, and Products - National Research Council (The National Academies Press, 2002)
Dramatic developments in understanding the fundamental underpinnings of life have provided exciting opportunities to make marine bioproducts an important part of the U.S. economy. Several marine based pharmaceuticals are under active commercial development, ecosystem health is high on the public's list of concerns, and aquaculture is providing an ever greater proportion of the seafood on our tables. Nevertheless, marine biotechnology has not yet caught the public's, or investor's, attention. Two workshops, held in October 1999 and November 2001 at the National Academies, were successful in highlighting new developments and opportunities in environmental and biomedical applications of marine biotechnology, and also in identifying factors that are impeding commercial exploitation of these products. This report includes a synthesis of the 2001 sessions addressing drug discovery and development, applications of genomics and proteomics to marine biotechnology, biomaterials and bioengineering, and public policy and essays contributed by the workshop speakers.

Review of the U.S. Navy Environmental Health Center's Health-Hazard Assessment Process - National Research Council (The National Academies Press, 2000)
A large number of chemicals are used on land at shore facilities, in the air in combat and reconnaissance aircraft, on seas around the world in surface vessels, and in submarine vessels by the navy and marine corps. Although the chemicals used are for the large part harmless, there is a significant amount of chemicals in use that can be health hazards during specific exposure circumstances. The Navy Environmental Health Center (NEHC) is primarily tasked with assessing these hazards. The NEHC completes its tasks by reviewing toxicological and related data and preparing health-hazard assessments (HHAs) for the different chemicals. Since the NEHC is continually asked to develop these HHAs, the National Research Council (NRC) was asked to assess independently the validity and effectiveness of NEHC's HHA process, in order to determine whether the process as implemented provides the Navy with the best, comprehensive, and defensible evaluations of health hazards and to identify any elements that might require improvement. The task was assigned to the Board on Environmental Studies and Toxicology's Committee on Toxicology's (COT's) Subcommittee on Toxicological hazard and Risk Assessment. Review of the U.S. Navy Environmental Health Center's Health-Hazard Assessment Process presents the subcommittee's report. The report is the work of expertise in general toxicology, inhalation toxicology, epidemiology, neurotoxicology, immunotoxicology, reproductive and developmental toxicology, pharmacology, medicine, risk assessment, and biostatistics. It is based on its review of documents provided by NEHC, presentations by NEHC personnel, and site visits to NEHC in Norfolk, Virginia and an aircraft carrier in San Diego, California.

Tracking Radiation Exposure from Medical Diagnostic Procedures: Workshop Report - National Research Council
The growing use of medical diagnostic procedures is correlated with tremendous and undeniable benefits in the care of most patients. However, it is accompanied by growing concerns about the risks associated with diagnostic computed tomography and other procedures that utilize ionizing radiation. A number of initiatives in radiation safety in medicine have taken place in the United States and internationally, each serving different purposes. Their ultimate goals are to provide higher quality clinical management of the patient and to ensure that reasonable steps are taken to keep the exposures as low as possible without compromising diagnostic efficacy. Tracking Radiation Exposure from Medical Diagnostic Procedures: Workshop Reports provides a summary of the presentations and discussions that took place during the December 8-9, 2011, workshop titled \

Toxicological Risks of Selected Flame-Retardant Chemicals - National Research Council (The National Academies Press, 2000)
Ignition of upholstered furniture by small open flames from matches, cigarette lighters, and candles is one of the leading causes of residential-fire deaths in the United States. These fires accounted for about 16% of civilian fire deaths in 1996. On average, each year since 1990, about 90 deaths (primarily of children), 440 injuries, and property losses amounting to 50 million dollars have resulted from fires caused by the ignition of upholstered furniture by small open flames. Certain commercial seating products (such as aircraft and bus seats) are subject to flammability standards and sometimes incorporate FR-treated upholstery cover materials, but there is no federal-government requirement for residential upholstered furniture, and it is generally not treated with FR chemicals. It is estimated that less than 0.2% of all U.S. residential upholstery fabric is treated with flame-retardant (FR) chemicals. The Consumer Product Safety Act of 1972 created the U.S. Consumer Product Safety Commission (CPSC) as an independent federal regulatory agency whose mission is to protect the public from unreasonable risks of injury and death associated with consumer products. CPSC also administers the Flammable Fabrics Act, under which it regulates flammability hazards and the Federal Hazardous Substances Act (FHSA), which regulates hazardous substances including chemicals. In 1993, the National Association of State Fire Marshals petitioned CPSC to issue a performance-based flammability standard for upholstered furniture to reduce the risk of residential fires. The Commission granted that portion of the petition relating to small open flame ignition risks. In response to concerns regarding the safety of FR chemicals, Congress, in the fiscal year 1999 appropriations report for CPSC, requested that the National Research Council conduct an independent study of the health risks to consumers posed by exposure to FR chemicals that are likely to be used in residential upholstered furniture to meet a CPSC standard. The National Research Council assigned the project to the Committee on Toxicology (COT) of the Commission on Life Sciences' Board on Environmental Studies and Toxicology. COT convened the Subcommittee on Flame-Retardant Chemicals, which prepared this report. Subcommittee members were chosen for their recognized expertise in toxicology, pharmacology, epidemiology, chemistry, exposure assessment, risk assessment, and biostatistics. Toxicological Risks of Selected Flame-Retardant Chemicals is organized into 18 chapters and two appendices. Chapter 2 describes the risk assessment process used by the subcommittee in determining the risk associated with potential exposure to the various FR chemicals. Chapter 3 describes the method the subcommittee used to measure and estimate the intensity, frequency, extent, and duration of human exposure to FR chemicals. Chapters 4-19 provide the subcommittee's review and assessment of health risks posed by exposure to each of the 16 FR chemicals. Data gaps and research needs are provided at the end of these chapters.

A Research Strategy for Environmental, Health, and Safety Aspects of Engineered Nanomaterials - National Research Council (The National Academies Press, 2012)
The nanotechnology sector, which generated about 225 billion in product sales in 2009, is predicted to expand rapidly over the next decade with the development of new technologies that have new capabilities. The increasing production and use of engineered nanomaterials (ENMs) may lead to greater exposures of workers, consumers, and the environment, and the unique scale-specific and novel properties of the materials raise questions about their potential effects on human health and the environment. Over the last decade, government agencies, academic institutions, industry, and others have conducted many assessments of the environmental, health, and safety (EHS) aspects of nanotechnology. The results of those efforts have helped to direct research on the EHS aspects of ENMs. However, despite the progress in assessing research needs and despite the research that has been funded and conducted, developers, regulators, and consumers of nanotechnology-enabled products remain uncertain about the types and quantities of nanomaterials in commerce or in development, their possible applications, and their associated risks. A Research Strategy for Environmental, Health, and Safety Aspects of Engineered Nanomaterials presents a strategic approach for developing the science and research infrastructure needed to address uncertainties regarding the potential EHS risks of ENMs. The report summarizes the current state of the science and high-priority data gaps on the potential EHS risks posed by ENMs and describes the fundamental tools and approaches needed to pursue an EHS risk research strategy. The report also presents a proposed research agenda, short-term and long-term research priorities, and estimates of needed resources and concludes by focusing on implementation of the research strategy and evaluation of its progress, elements that the committee considered integral to its charge.

A Review of the Draft Report of the NCI-CDC Working Group to Revise the 1985 Radioepidemiological Tables - National Academy of Sciences
The National Research Council was asked by the Centers for Disease Control and Prevention (CDC) to review the draft report of the National Cancer Institute (NCI)-CDC's working group charged with revising the 1985 radioepidemiological tables. To this end, a subcommittee was formed consisting of members of the Council's Committee on an Assessment of the Centers for Disease Control and Prevention Radiation Programs and other experts. The original tables were mandated under Public Law 97-414 (the \

Review of Studies of Possible Toxic Effects from Past Environmental Contamination at Fort Detrick: A Letter Report - National Research Council (The National Academies Press, 2012)
Fort Detrick's Area B has been used for disposal of chemical, biological, and radiological material, storage of explosives, and research activities. The groundwater of Area B was contaminated by perchloroethylene (PCE) and trichloroethylene (TCE), which leaked from storage drums buried in Area B. Members of the public who live near Fort Detrick in Frederick County, Maryland, are concerned that the contaminated groundwater might have affected their health. This report reviews two investigations of potential health hazards: a 2009 public health assessment conducted by the Agency for Toxic Substances and Disease Registry and a cancer investigation in Frederick County by the Maryland Department of Health and Mental Hygiene and the Frederick County Health Department.

Carcinogens and Anticarcinogens in the Human Diet: A Comparison of Naturally Occurring and Synthetic Substances - National Research Council (The National Academies Press, 1996)
Despite increasing knowledge of human nutrition, the dietary contribution to cancer remains a troubling question. Carcinogens and Anticarcinogens assembles the best available information on the magnitude of potential cancer risk2014and potential anticarcinogenic effect2014from naturally occurring chemicals compared with risk from synthetic chemical constituents. The committee draws important conclusions about diet and cancer, including the carcinogenic role of excess calories and fat, the anticarcinogenic benefit of fiber and other substances, and the impact of food additive regulation. The book offers recommendations for epidemiological and diet research. Carcinogens and Anticarcinogens provides a readable overview of issues and addresses critical questions: Does diet contribute to an appreciable proportion of human cancer? Are there significant interactions between carcinogens and anticarcinogens in the diet? The volume discusses the mechanisms of carcinogenic and anticarcinogenic properties and considers whether techniques used to evaluate the carcinogenic potential of synthetics can be used with naturally occurring chemicals. The committee provides criteria for prioritizing the vast number of substances that need to be tested. Carcinogens and Anticarcinogens clarifies the issues and sets the direction for further investigations into diet and cancer. This volume will be of interest to anyone involved in food and health issues: policymakers, regulators, researchers, nutrition professionals, and health advocates.

Industrial Research Laboratories of the United States, Including Consulting Research Laboratories - National Research Council (The National Academies Press, 1946)

Effects of a Polluted Environment: Research and Development Needs - National Research Council (The National Academies Press, 1977)

Gender Differences in Susceptibility to Environmental Factors: A Priority Assessment - Institute of Medicine (The National Academies Press, 1998)
Women's health and men's health differ in a variety of ways2014women live longer on average, for example, but tend to be sicker as well. Whereas some of these distinctions are based solely on gender, there is growing awareness that the environment and related factors may play a role in creating health status differences between men and women. Various factors, such as genetics and hormones, may account for gender differences in susceptibility to environmental factors. In 1996 the Office for Research on Women's Health at the National Institutes of Health asked the Institute of Medicine to conduct a workshop study to review some of the current federal research programs devoted to women's health and to clarify the state of knowledge regarding gender-related differences in susceptibility. This book contains a general outline of research needs, a summary of the workshop proceedings (as well as summaries of the speakers' presentations), and an analysis of the participating federal agencies' research portfolios.

Status of Research in Underwater Physiology, Prepared for the Office of Naval Research, Washington, D. C. by the Physiology Group, Panel on Underwater Swimmers, Committee on Undersea Warfare - National Research Council (The National Academies Press, 1956)